A Digital Media-Based Learning Transformation Strategy in an Effort to Implement Differentiated Learning at the PGRI Kamal Madura Special School - Prakoso, Albrian Fiky; Maghfiroh, Fitrania; Ghofur, Muhammad Abdul; Andriansyah, Eka Hendi; Kamalia, Putri Ulfa; Roziqifath, Zain Fuadi Muhammad; Ginanjar, Ardhita Eko; Wafi, Ahmad Yusronil (Indonesian Journal of Society Development, 2024)
This community service that aims to improve teachers' ability to use technology in Special School PGRI Kamal. In the initial observation, the results were obtained that there were various challenges faced by the teacher council at Special School PGRI Kamal in the implementation of learning for students with special needs such as the deaf and speech-impaired. The limited number of teachers which causes an additional workload for teachers. Community service activities are needed by providing workshops. The workshop  activities held included the use of audio, visual, and audiovisual media which were carried out offline. The workshop held in this service program is expected to improve teachers' skills in the use of  digital media platforms to support learning activities